Hydrogenation-induced lattice expansion and its effects on hydrogen diffusion and damage in Ti–6Al–4V. (15th April 2020) - Kim, Jinwoo; Plancher, Emeric; Tasan, C. Cem
Abstract: Hydrogen uptake in titanium alloys leads to the formation of hydride phases, which in-turn cause severe embrittlement upon further deformation. The embrittlement micro-mechanisms are complicated by the distinct hydrogen diffusion and solution characteristics of the α and β phases, which arise from their different crystal structures. To improve the fundamental understanding of the room temperature interplay among hydrogen, the present phases and the hydride that is formed at their interface, we investigated the hydride formation process in Ti–6Al–4V alloy by in situ scanning electron microscopy and electron backscatter diffraction analyses during hydrogen charging, and post-mortem synchrotron diffraction tests. These investigations reveal that the lattice expansion of the hydrogenated β phase introduces a localized stress field near the phase boundary, which, in turn, induces hydrogen confinement therein, eventually facilitating the hydride growth along the boundary. The volumetric expansion of the α-to-hydride transformation extends the local stress field, influencing the work-hardening and damage evolution in the alloy. We discuss these findings and the overall damage initiation and propagation taking place in the hydrogenated alloy, based on the interplay among the present phases and hydrogen. Graphical abstract: Image, graphical abstract